Bezlotoxumab for Prevention of Recurrent Clostridioides difficile Infection With a Focus on Immunocompromised Patients. (June 2023) - Askar, Sally F.; Kenney, Rachel M.; Tariq, Zain; Conner, Ruth; Williams, Jonathan; Ramesh, Mayur; Alangaden, George J.
Objectives: Approximately 25% of patients with Clostridioides difficile infection (CDI) will experience recurrence, which is greater in immunocompromised patients. We report experience with an institutional guideline targeting high-risk immunocompromised patients.Methods: This was a retrospective cohort of consecutive patients with CDI who met institutional criteria for bezlotoxumab due to high risk for recurrent CDI between June 1, 2017, and November 30, 2018. The primary endpoint of recurrent CDI within 12 weeks was compared between patients who received the standard of care (SoC) plus or minus bezlotoxumab.Results: Twenty-three patients received bezlotoxumab infusion plus SoC and were compared to 30 SoC patients. 84% of patients were immunocompromised and 54.7% were transplant recipients. The primary endpoint occurred in 13% of bezlotoxumab patients compared to 23.3% of SoC patients. No serious adverse effects were identified.Conclusion: Bezlotoxumab was associated with a meaningful reduction in recurrent CDI in this cohort largely comprising immunocompromised and transplant patients. Larger studies are warranted to evaluate bezlotoxumab in this population.